Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1037/h0087122
|View full text |Cite
|
Sign up to set email alerts
|

The Parenting Sense of Competence scale: Evidence of a stable factor structure and validity.

Abstract: In this study, 110 mothers and 110 fathers of 5-to 12-yearold boys and girls completed the Parenting Sense of Competence (PSOC) scale and measures of child behaviour, parenting style, and marital satisfaction. We replicated the factor structure of the Parenting Sense of Competence Scale produced by Johnston and Mash (1989), and provided evidence that the Satisfaction and Efficacy scales from this measure assess distinct aspects of parenting selfesteem. Interestingly, parents of girls reported higher Efficacy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
280
8
29

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(334 citation statements)
references
References 27 publications
17
280
8
29
Order By: Relevance
“…A strength of the current study was the use of a standardised measure of parental competence (PSOC) that has reported significant reliability and validity and assesses distinct aspects of parental self-esteem (Ohan et al, 2000). Another asset was the use of manualised intervention programmes that can be copied in other contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strength of the current study was the use of a standardised measure of parental competence (PSOC) that has reported significant reliability and validity and assesses distinct aspects of parental self-esteem (Ohan et al, 2000). Another asset was the use of manualised intervention programmes that can be copied in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The PSOC version used in the current study has 16 assertions that reflect parental self-perceptions of skills and knowledge regarding parental functions (Johnston & Mash, 1989). These assertions yield a satisfaction subscale that captures how pleased parents are with their parenting role and an efficacy scale that captures how parents perceive their competence in the parenting role (Ohan, Leung, & Johnston, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…U tom istraživanju nije utvrđena veza između mjerenih aspekata bračnih odnosa i roditeljske kompetentnosti, pa autori zaključuju da je samo afektivna komponenta doživljaja roditeljstva povezana s bračnim procesima unutar obitelji. Povezanost bračnoga zadovoljstva i zadovoljstva roditeljstvom može se objasniti i time da roditelji koji doživljavaju veće zadovolj-stvo u svojem partnerskom odnosu mogu bolje funkcionirati u roditeljskoj ulozi, jer skladan partnerski odnos podrazumijeva i bolje slaganje oko roditeljskih pitanja, odgojnih utjecaja i odnosa na relaciji roditelj -dijete (Ohan, 2000.). Stoga ne treba čuditi ova značajna korelacija.…”
Section: Raspravaunclassified
“…It consists of 16 items rated on a 6-point Likert scale (6 = strongly disagree, 1 = strongly agree). Internal consistency (25), convergent and discriminant validity (34,35), and reliability have been shown to be satisfactory (33). High scores indicate higher satisfaction and higher efficacy, respectively.…”
Section: The Screen For Child Anxiety Related Emotional Disorders (Scmentioning
confidence: 99%